NEW CEPHALOSPORIN AS AN ALTERNATIVE FOR TREATMENT OF INFECTIONS BY METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) - Bruna Gerardon Batista (Universidade de Santa Cruz do Sul, 2015)
Background and Objectives: The increased incidence of multiresistant microorganisms allied with the emergence of new mechanisms of bacterial resistance has ted treatment-related health care infections. Staphylococcus aureus has shown therapeutic limitations due to high prevalence of isolates resistant to methicillin (MRSA). The constant evolution of microorganisms in relation to antimicrobial susceptibility and rapid dissemintaion requires the introduction of new drugs in clinical practice to control infections caused by multiresistant microorganisms. In recent years, it has developed a limited number of new antimicrobial agents, among them are the 5th generation cephalosporins, ceftobiprole and ceftarolina, which have proven effective against MRSA isolates. The aim of this study was to review the literature about the characteristics and evolution of resistance in S. aureus, and about new antimicrobials used in clinical practice, featuring the main advantages and limitations of current treatment options. Methods: A literature review was performed in the MEDLINE and Scielo with papers published until the year 2014 survey was grouped according to the thematic focus following: cephalosporins, methicillin-resistant Staphylococcus aureus, combined modality therapy. Results: This study included nine scientific papers published in national and international journals for review. The articles included in this review were selected according to the information that is desired to be obtained, as follows regarding the use of antimicrobials in new anti-MRSA therapy, the main features and the advantages and limitations of current alternatives vailable. Conclusion: It is concluded that cephalosporins 5th generation is a viable therapeutic option due to the satisfactory results reported in different studies to the treatment of infections, with each hospital, determine and adapt in their clinical practice, the use of new options treatment of MRSA infections. Keywords: Cephalosporins. Methicillin-resistant Staphylococcus aureus. Combined Modality Therapy.